Information representation and retrieval in nanoengineering applications. (2018) - Shakhnov, V.A.; Zinchenko, L.A.; Rezchikova, E.V.; Kishinevsky, A.K.; Sorokin, B.S.
In the paper, we discuss some approaches to information representation and retrieval for nanoengineering applications. Cognitive features of human recognition are outlined. We review 3D visualisation technologies and their application in nanoengineering. A hybrid virtual reality system for nanoengineering applications is proposed. A converter transforming the 3D active input signal to the 3D passive output signal is presented. We discuss some different approaches to information granulation for complex nanoobjects as well. Finally, we give advantages of visual analytics support systems in nanoengineering.